Innovative online platform to support communication for persons with obesity: STOP Portal: Presenter(s): Anne Moorhead, Ulster University, United Kingdom. (April 2023) - Zheng, Huiru (Jane); Lynch, Louise; D'Arco, Luigi; Bond, Raymond; Wang, Haiying; Vu, Binh; Hemmje, Matthias; Mertens, Jana; Engel, Felix
Abstract : Background: Persons with obesity requires support, including updated and regular communication in order to make informed lifestyle choices. The STOP project, a H2020 RISE project funded by European Commission (GA No 823978) aims to establish a data and knowledge ecosystem as a basis for the STOP Portal to enable healthcare professionals in decision support, and persons with obesity. The aim of this current study was to test the feasibility of the STOP Portal for ease of use, and to validate its functions. This paper focuses on the communication-related findings. Methods: This is a feasibility study for the STOP Portal. The participants were adults who are overweight and obese. The STOP Portal collects the following data: knowledge resources, and physiological, activity and food data. Participants accessed the STOP Portal for one week and recorded their activity and food intakes. Data were sought from the platform to gain a more complete understanding of participation and engagement. Data were analysed using SPSS and content analysis. Results: From the preliminary results, 31 participants registered for the STOP Portal and 24 used it for up to one week. From these 24 participants, they found the Portal was acceptable and easy to use. Factors influencing motivation and engagement to participate were: 1. social support; 2. technical issues; and 3. time. The Portal was able to collate information from other sources such as wearable wrist bands or apps in monitoring the activities along with inputted data to provide informative, educational and motivational messages for the participants. Conclusion: The STOP Portal has potential and is deemed acceptable and fit for purpose to collect activity and food data from a range of sources to communicate messages to people with obesity to inform their lifestyle choice decision making. Further research is ongoing to establish the effectiveness of the STOP Portal.